Komunikasi Singkat: Deteksi Serotipe Avibacterium Paragallinarum Dari Isolat Unggas Ladang Indonesia Menggunakan Hemagglutination Inhibition Test - A.E.T.H. Wahyuni; Fadhli Nanda Putra; Low Kar Yee; Tan Yun Ru; Cheng Ern Wei; Yahya Pambudhi; Puteri Nur Natasha (IPB University, 2022)
Infectious coryza (IC) is an opportunistic and infectious upper respiratory tract disease in poultry, caused by Avibacterium paragallinarum. This disease has high morbidity but low mortality. The major losses caused by IC are the reduced egg production and increased feed conversion ratio (FCR). There are three recognized Avibacterium paragallinarum serovars, which are serovar A, B, and C. Limited reports regarding the serovars of Avibacterium paragallinarum in Indonesia are available. This research was done to detect the serovar of Avibacterium paragallinarum from Indonesian poultry field isolate using hemagglutination inhibiotion (HI) test. Ten field isolates of Avibacterium paragallinarum were re-identified, then processed into antigen solution using sonication, further on used for hemagglutination (HA) test. After the 4HA unit titer was obtained, the antigens were tested with HI using reference antisera (Strain 221 serovar A, strain Spross serovar B, and strain Modesto, serovar C). The results showed that one isolate had the highest titer with antiserum serovar A which was >5120 HI unit and nine isolates had the highest titer with antiserum serovar B which was >5120 HI Unit. Therefore, it can be concluded that one field isolates of Avibacterium paragallinarum from layer chicken is serovar A and nine field isolates of Avibacterium paragallinarum from layer, broiler, free range chicken, quail field isolates are serovar B.